GAMBARAN KUALITAS TIDUR PADA ANAK DENGAN PENYAKIT AKUT - Melvi " Gustiarinni; Ganis " Indriati; Wan Nishfa Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Sleep is one of the basic human needs. Sleep quality is important for health and healing from a illness. Illness can cause many effects to children, one of them is the children have lack of sleep or even can not sleep at all. Sleep disturbance cause various negative effect for children’s growth and development. The aim of this research was to determine sleep quality in children with acute pain. The research used descriptive design. The research was conducted in Public Health Center Simpang Tiga through 144 respondents that taken by purposive sampling technique. The instrument was The Children’s Sleep Habits Questionnaire (CSHQ) with 16 items consist of 4 domains: bedtime, sleep behavior, waking during the night, and morning waking. Data analisys used univariate to determine characteristic and sleep quality of respondents. The most characteristic respondents were preschool children wich age 3-5 years (52,1%), the most of participants were female (52,1%), the most participants have fever as illness (45,1%). The result of this research represents total sleep quality are disorders (56,9%) wich are bedtime, sleep behavior, waking during the night, and morning waking. This research recommends to nurse in Public Health Center to concerned with sleep quality in children. Keywords                     : acute pain, preschool children, sleep quality,